Antibacterial activities of purified monolaurin obtained from enzymatic glycerolysis of palm kernel olein-stearin blend against Bacillus subtilis - Ngatirah Ngatirah; Chusnul Hidayat; Endang Sutriswati Rahayu; Tyas Utami (Applied Food Biotechnology, 2023)
Background and Objective: Monolaurin can be produced by enzymatic glycerolysis of a mixture of palm kernel olein-stearin (PKOo-PKS). Monolaurin has the ability as an antibacterial agent against both gram-positive and negative bacteria. Limited studies investigated the activity against bacteria of monolaurin on B. subtilis cell and spores. Therefore, this research aimed to study the effect of a purified monolaurin obtained from enzymatic glycerolysis of PKOo-PKS blend on growth, spore germination, cell surface hydrophobicity, and cell structure of B. subtilis FNCC 0060.